2001
DOI: 10.1677/joe.0.1700485
|View full text |Cite
|
Sign up to set email alerts
|

Familial resemblance for free androgens and androgen glucuronides in sedentary black and white individuals: the HERITAGE Family Study. Health, Risk Factors, Exercise Training and Genetics

Abstract: Familial correlation analyses were used to evaluate the familial aggregation of plasma androgens and androgen glucuronides (testosterone (TESTO), dihydrotestosterone (DHT), androstane-3 ,17 -diol glucuronide (3 -DIOL-G), and androsterone glucuronide (ADT-G)) in 505 members of 99 white families and 296 members of 111 black families participating in the Health, Risk Factors, Exercise Training and Genetics (HERITAGE) Family Study. Each of these four measures was determined by RIA after separation of conjugated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
2
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
3
24
2
1
Order By: Relevance
“…The sex difference in heritability has also been found for several other traits 9. In addition, previous studies also found a higher heritability of testosterone, IgA, IgE, IgG and IgM levels in males than females 14 22. It is likely that there may be shared common causes between metabolic syndrome and immunity response.…”
Section: Discussionmentioning
confidence: 76%
“…The sex difference in heritability has also been found for several other traits 9. In addition, previous studies also found a higher heritability of testosterone, IgA, IgE, IgG and IgM levels in males than females 14 22. It is likely that there may be shared common causes between metabolic syndrome and immunity response.…”
Section: Discussionmentioning
confidence: 76%
“…Baseline testosterone has fairly high heritability. The majority of estimates are between 50 percent and 70 percent with a mean of 60 percent (e.g., Gagnon et al 2001;Harris and Vernon et al 1998).…”
Section: Primer On Testosteronementioning
confidence: 99%
“…For example, the heritability of neuroticism, a personality trait, was estimated to range from 13 to 58% [18] . In men, heritability estimates are in the range of 25-75% for testosterone [19][20][21][22][23][24] . Some traits, such as height and hemoglobin concentration, have heritability of 80% or above [25,26] .…”
Section: Simulation Designmentioning
confidence: 99%